Iraq’s swamps and surrounding pests - Mustafa Ali Al Sharoot; Bashar Abd Alkadhim Naji; Alrabab Tariq AbdulKarim (Eximia, 2024)
According to the results of a study conducted on the types of mosquitoes prevalent in certain parts of the Al-Qadisiyah Governorate, the following types of mosquitoes exist: There are Culisetea longiareolata, Obadiah spp., Aedes detritus, Cx. molestus, and the Asian tiger mosquito. The presence of mosquitoes reached molestus, where the highest concentrations of Cx. molestus were recorded in the neighbourhoods of Al-Hakim, Al-Orouba, Al-Tali’a, and Al-Hamza Al-Sharqi, 84%, 76%, 72%, and 50%, respectively. To mimic mosquito infestation and control, this study will create a mathematical model considers environmental factors, including wind, temperature, and terrain features. We paid special attention to the Asian tiger mosquito, which is now known to be a significant carrier of human illnesses such as dengue , yellow fever, and chikungunya. The management of disease vectors is one method for preventing such epidemics. As an alternative to chemical control methods that are extremely detrimental to the environment, biological control methods such as the insect technique (SIT) are of great interest. The success of SIT depends on accurate modelling of insect dispersion as well as solid knowledge of insect biology. To predict mosquito dispersal, we take into account a piecemeal approach and build temporal, spatial, and temporal models employing susceptibility, diffusion, and interaction equations. A propulsive differential equation is used to represent the release of infertile males on a regular basis. Finally, we offer numerical simulations of mosquito dispersal and assess several vector control scenarios utilizing a split factor approach and numerical approaches that are ideally suited to each operator. We demonstrate how the environment can have a significant impact on mosquito dispersal as well as the effectiveness of vector control techniques such as SIT.